4TRAINING (CIPEEX, 2025)
4Training connects personal trainers with students independently from gyms, allowing users tomaintain workout history and progress across multiple trainers or gyms. It solves the commonissue of geographic limitations for trainers, enabling them to train students from anywhere andexpand their reach and growth potential. The app creates a seamless, multi-sport profile thatintegrates training history and progress into one digital space, enhancing user engagementand motivation. Using Design Thinking, the core issue of trainers' reliance on local gyms forclients was identified. 4Training provides a solution that allows trainers to scale their clientelewithout geographic restrictions, filling a niche in the market by offering an integratedexperience that benefits both trainers and students.
Keywords: connects; personal; gyms; digital space